2022
DOI: 10.1007/s11661-022-06864-2
|View full text |Cite
|
Sign up to set email alerts
|

Development and Investigation of Mesoporous Bioactive Glass/Zein Coatings Electrodeposited on Titanium Alloy for Biomedical Applications

Abstract: The objective of the present work was the development of cathodic electrophoretic deposition (EPD) to obtain composite coatings of mesoporous sol–gel glass (MSGG) particles embedded in a zein matrix on Ti-13Nb-13Zr substrates. To deposit robust and repeatable coatings, a direct current EPD and pulsed direct current EPD as well as the deposition kinetics were investigated, including the deposition yield and deposition rate. The stability of the suspension was determined based on the zeta potential and conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 82 publications
0
10
1
Order By: Relevance
“…Despite the low stability of the suspensions, coatings were satisfactorily deposited on the cathode. As we described in a previous paper, 47 the mechanism of coating deposition, in which zein binds to MSGG particles, has a significant influence. A similar mechanism occurred in the co-deposition of zein with the MSGG-Cu and MSGG-Cu-Mg particles.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Despite the low stability of the suspensions, coatings were satisfactorily deposited on the cathode. As we described in a previous paper, 47 the mechanism of coating deposition, in which zein binds to MSGG particles, has a significant influence. A similar mechanism occurred in the co-deposition of zein with the MSGG-Cu and MSGG-Cu-Mg particles.…”
Section: Resultsmentioning
confidence: 77%
“…24,26,53 Additionally, the incorporation of glycerin into the solution increases the plasticity of the zein formed base of the coatings. 54 In our earlier work, 47 we showed that the solution of EtOH/H 2 O in the ratio of 9/1 and 0.024 kg dm −3 glycerol, 0.2 kg dm −3 zein and 0.04 kg dm −3 reference MSGG is optimal for the fabrication of uniform MSGG/zein coatings with high adhesion to the substrates. Therefore, to study the effect of the incorporation of Cu and Mg to glasses on EPD in this study, zein solutions with MSGG-Cu and MSGG-Cu-Mg particles in various contents, but the same as in the case of reference MSGG, 47 0.01 kg dm −3 , 0.04 kg dm −3 and 0.08 kg dm −3 , were used.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Physical, structural condition Amorphous [28] Denaturation (°C) 80.32-87.31 [29] Glass transition (°C) 165 [30,31] Melting point (°C) 266-283 [32] Thermal degradation (°C) 320 [30,33] Degree of polymerization 210-245 [17] Isoelectric point pH 6.2 [34] Density (g cm −3 ) 1 . 2 3 g c m −3 [35,36] Partial specific volume 0.771 [37] Particle size (nm) 150-550 [38][39][40] Water content (g/100 g) 10.5, at a water activity of 0.753 in 25 °C [41] Solubility Almost impossible to dissolve in 100% ethanol, acetone, or water; Soluble in acetone solutions (60-80% v/v), extremely concentrated urea, and glycols; Soluble in alkaline solutions of pH ≥ 11.5 [20,35,42] Viscosity coefficient 25 [43] Diffusion coefficient (m 2 s −1 ) 3.7× 10 −14 [43] Flavor Tasteless [44] Odor Odorless [45] Color Yellowish [46] Composition (%) Glutamine 21-26 Proline 10 Leucine 20 Alanine 10 [47] zein is easily transformed into nanofibers, nanoribbons, [53] nanoparticles, [54] microspheres, [55] thin coatings, [56] and Janus fibers. [57] Zein possesses exceptional characteristics like flexibility, high surface area, low cytotoxicity, biocompatibility, and biodegradability.…”
Section: Properties Characteristics Referencesmentioning
confidence: 99%